Development and Validation of the Secondary Transition Fidelity Assessment - Lombardi, Allison R.; Rifenbark, Graham G.; Poppen, Marcus; Reardon, Kyle; Mazzotti, Valerie L.; Morningstar, Mary E.; Rowe, Dawn; Raley, Sheida K. (Assessment for effective intervention, 2022)
In this study, we examined the structural validity of the Secondary Transition Fidelity Assessment (STFA), a measure of secondary schools’ use of programs and practices demonstrated by research to lead to meaningful college and career outcomes for all students, including students atrisk for or with disabilities, and students from diverse backgrounds. Drawing from evidence-based practices endorsed by the National Technical Assistance Center for Transition and the Council for Exceptional Children’s Division on Career Development and Transition, the instrument development and refinement process was iterative and involved collecting stakeholder feedback and pilot testing. Responses from a national sample of educators (N = 1,515) were subject to an exploratory factor analysis resulting in five measurable factors: (a) Adolescent Engagement, (b) Inclusive and Tiered Instruction, (c) School-Family Collaboration, (d) District-Community Collaboration, and (e) Professional Capacity. The 5-factor model was subject to a confirmatory factor analysis that resulted in good model fit. Invariance testing on the basis of geographical region strengthened validity evidence and showed a high level of variability with regard to implementing evidence-based transition services. Findings highlight the need for consistent and regular use of a robust, self-assessment fidelity measure of transition service implementation to support all students’ transition to college and career.